EFFECT OF SECANG WOOD (CEASALPINIA SAPPAN L.) EXTRACT ON MORPHOLOGY OF SPERMATOZOA, SPERM COUNT, AND REVERSIBLE PROCESS IN MALE RATS - Silfia Sekar Arum; Syarief Thaufik Hidayat; Nur Khafidhoh; Suryati Kumorowulan; Suhartono Suhartono; Ari Suwondo (Belitung Nursing Journal, 2017)
Background: Limited choice of contraception for males is one of the reasons why their participation is low. Secang wood is considered as an alternative contraception that has an influence in the morphology and number of spermatozoa and reversible in nature. Objective: To examine the effect of extracts of secang wood in the morphology of spermatozoa, sperm count and reversible process in male mice. Methods: This was a quasi-experimental study with randomized posttest only control group design. There were 32 male rats (Mus Muscullus L) recruited in this study. Four groups were involved, namely: 1) ethanol group, 2) chloroform fraction, 3) water fraction, and 4) control group. Each group consisted of 8 mice. There were two treatments in this study: 1) each group was given secang extract with dose 50 mg/25 gram of weight, 2) the observation period was 10 days after the treatment. Four mice in each group was dissected to see the morphology and sperm count while the other four mice were allowed to live and maintained until 20 days to see reversible morphology and sperm count. Results: The extract of secang wood at a dose of 50mg/25gram weight could increase the abnormal sperm morphology and lower sperm count. There was a significant difference between the treatment group and control group with p-value <0.05. The extract was also reversible on the morphology and sperm count. Conclusion: There was a significant effect of secang wood extract on sperm morphology, the number of spermatozoa, and reversible process. This study provides the insight of scientific information about the effect of the secang extracts on the number and morphology of spermatozoa, and it could be used as a basis for further research in human in the development of natural contraceptive on a reversible man.